Criminalistics and Crime Scene Investigation in Microgravity Space - Ardacan Tan, Görkem (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2024)
Addresses the challenges and considerations of criminalistics and crime scene investigation in extraterrestrial gravitational environments. Future space exploration may require the development of protocols for extraterrestrial crime scene investigations. Challenges in microgravity effects, confined space environments, forensic techniques, communication, coordination, and legal jurisdiction are highlighted in this brief. Microgravity effects create difficulties in displacing evidence, such as blood spatter patterns, which make interpretation of events difficult. Restricted areas such as spacecraft and stations require special techniques and equipment. Storing and securing evidence in microgravity makes traditional methods impractical. The lack of gravity affects fingerprint development and preservation, requiring the use of alternative methods. Compact and specialized equipment is required to analyze DNA in space. Communication delays hinder real-time collaboration between researchers on Earth and those in space. Guidance can be provided to personnel in space with remote technologies and autonomous systems. Determining legal jurisdiction for crimes committed in space or on spacecraft requires complex international cooperation and agreements. The development of space law, technology and international agreements is important to meet the challenges of extraterrestrial crime scene investigations. Future discussions and research will provide a basis for establishing protocols for extraterrestrial crime scene investigations to ensure effective and fair forensic practices. As space exploration progresses, advances need to be made in these areas. As space exploration advances, the development of space law, technology, and international agreements is crucial to meeting the unique challenges of extraterrestrial crime scene investigations. This summary provides a basis for future discussions and research regarding the establishment of protocols to ensure effective and fair forensic practices off Earth.
he disciplines of criminalistics and crime scene investigation, forensic science and space research in space are developing by merging and progressing in the future. However, it should be taken into consideration that crimes are committed in space and due to the micro-levels of gravity, and even due to the human factor that will increase with the increasing astronomy and space science in space where there is no gravity. It should be known how criminalistic and crime scene investigations should be carried out due to the possibility of any incident occurring in space as people are included in space and mission periods are extended. It is necessary to express the problem of uncertainty in the processes of crime scene investigation and criminalistic techniques in space, collecting, examining and analyzing scientific evidence for the purpose of solving the causes or qualities that can be considered forensic in any criminal activity or accident. In order to understand the investigation of crime scenes of different types and sizes in space, it is necessary to first know enough information about space and understand what kind of challenges the potential risks pose from a criminalistic perspective. The basis of these risks is living in space, working in an environment with microgravity, exposure to radiation and working in a closed environment, that is, in space vehicles, are some of the inherent dangers. In addition, some of the other dangerous situations that may occur inside and outside spacecraft are equipment malfunctions, medical emergencies and even intentional sabotage. Another problem in space is the knowledge of space researchers in criminalistics and crime scene investigation. It is important that forensic astronauts are trained to be able to conduct crime scene investigations in space, collect valuable evidence, and reconstruct the incident sequence to determine the cause or identify the people involved. Unlike Earth, 90 percent of gravity in space is reduced to microgravity. Microgravity, which begins in Earth orbit and continues in space, may vary depending on environmental conditions, that is, according to research conducted in space geology. In this case, microgravity brings differences from standard environmental conditions in the evaluation of physical events by astronauts or forensic astronauts and criminal crime scene investigators. For example, blood spatter patterns may differ in microgravity conditions. This presents special challenges that must be taken into account in scientific and forensic analyzes of events occurring in space 4 . With all this, examining crime scenes in space poses different challenges and risks compared to some traditional crime scenes, as well as physical, chemical, biological and geological conditions on Earth. For example, the absence of gravity and its presence at micro levels affects the movement and interaction of objects, making it difficult to determine the exact trajectory of bullets or the location of evidence or evidence at the time of the incident. Additionally, the absence or limited availability of vehicles and supplies in space may hinder the collection and preservation of evidence due to limited equipment and equipment. Astronaut forensic investigators must develop new techniques and adapt their practices to the environment, using new methods to effectively secure and analyze evidence. Overcoming such challenges is crucial to the successful investigation of emerging criminal activity or accidentrelated investigations.
Keywords: Criminalistics; Microgravity; Crime Scene Investigation; Space; Gravity